EDUCATION FOR SUSTAINABLE DEVELOPMENT IN THE CURRICULAR CONTEXT OF THE PUBLIC SCHOOL SYSTEM OF THE STATE OF SAO PAULO: A BRIEF REFLECTION BY THE PERSPECTIVE OF UNITED NATIONS DECADE OF EDUCATION FOR SUSTAINABLE DEVELOPMENT - UNESCO (2005-2014) - Bastos, Alexandre Marucci [UNESP]; Lemes, Sebastiao de Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2015)
The institution of the United Nations Decade of Education for Sustainable Development (UN DESD) was approved on December 20, 2002, at the 57th Session of the UN General Assembly, at which it was decided to proclaim the ten-year period - beginning on 1 January 2005 until the end of 2014 - so that education was emphasized as an indispensable element for achieving sustainable development. In this context, this paper presents a discussion of how such a proposition UN was being treated by the curricular standards of public schools managed by the State Government of Sao Paulo in the last two years of the DESD. For both developed an analysis of curriculum guidelines outlined by the respective State Education Department, verifying that the same point would be aligned in relation to the purposes of the DESD, especially regarding dynamic curriculum of the public school system of the state government.
Keywords: Decade; United Nations; Education; Sustainable Development; Curriculum